Green beans Obonuco Andina and Obonuco San Isidro as productive alternatives for the substitution of illicit crops in the south of Colombia (2019)
The objective of this retrospective qualitative research was to reveal the effects perceived by peas producers in the municipality of Puerres located in the Department of Nariño (Colombia), after the adoption of varieties of pea (Pisum sativum) Obonuco Andina and Obonuco San Isidro. For this reason, a process of participatory construction was carried out with rural and indigenous population, with whom the productive, sociocultural and environmental dynamics of the territory were analyzed. The study covered the period between 1980 and 2017 which allowed us to determine the perception of the two focus groups against the mentioned dimensions and their effects on the territory. The results indicate that, in addition to the agronomic attributes of the two varieties under study and their acceptance in the market, aspects were presented that pressed the territory and acted as catalysts for its adoption. Likewise, it was determined that, in addition to the productive reconversion of cereal crops, these varieties were established as the productive option both economically and socially sustainable, given the need for the substitution of illegal crops in southern Colombia.